A visit to The Star Information Centre The Star Publications Sdn Bhd, Petaling Jaya (PPM Jelajah Digital Siri 3) / Kasmarini Baharuddin, Zati Atiqah Mohamad Tanuri and Fuziah Mohd Nadzar - Baharuddin, Kasmarini; Mohamad Tanuri, Zati Atiqah; Mohd Nadzar, Fuziah (2011)
On 8th March 2011, Persatuan Pustakawan Malaysia (PPM) organized a program of visit called "Jelajah Digital Siri 3" to The STAR Information Centre, located at The STAR Tower, Petaling Jaya. Assoc. Prof Fuziah Haji Mohd Nadzar and her two mentees, Kasmarini Baharuddin and Zati Atiqah Tanuri, from the Faculty of Information Management, UiTM Puncak Perdana, had joined the program to obtain first-hand exposure and experience pertaining to the digitizing process and procedures of this newspaper library. About 30 librarians from various libraries including Perpustakaan Negara Malaysia, Bernama Library, Utusan Library, Astro Library, etc. had participated in this visit. PPM's own executive officer had joined this visit too.